The effects of femoral graft placement on in vivo knee kinematics after anterior cruciate ligament reconstruction - Abebe, E S (2011)
Achieving anatomical graft placement remains a concern in anterior cruciate ligament (ACL) reconstruction. The purpose of this study was to quantify the effect of femoral graft placement on the ability of ACL reconstruction to restore normal knee kinematics under in vivo loading conditions. Two different groups of patients were studied: one in which the femoral tunnel was placed near the anterior and proximal border of the ACL (anteroproximal group, n=12) and another where the femoral tunnel was placed near the center of the ACL (anatomic group, n =10) MR imaging and biplanar fluoroscopy were used to measure in vivo kinematics in these patients during a quasi-static lunge. Patients with anteroproximal graft placement had up to 3.4mm more anterior tibial translation, 1.1mm more medial tibial translation and 3.7° more internal tibial rotation compared to the contralateral side. Patients with anatomic graft placement had motion that more closely replicated that of the intact knee, with anterior tibial translation within 0.8mm, medial tibial translation within 0.5mm, and internal tibial rotation within 1°. Grafts placed anteroproximally on the femur likely provide insufficient restraint to these motions due to a more vertical orientation. Anatomical femoral placement of the graft is more likely to reproduce normal ACL orientation, resulting in a more stable knee. Therefore, achieving anatomical graft placement on the femur is crucial to restoring normal knee function and may decrease the rates of joint degeneration after ACL reconstruction.